Whole exome sequencing identifies concurrent LDLR and ABCG8 mutations in a Saudi family with familial hypercholesterolemia and Sitosterolaemia - Hummadi, Abdulrahman; Mutawwam, Dhayf Alrahman; Banaganapalli, Babajan; Alsubhi, Fai; Aljohani, Naji J.; Alhagawy, Ali J.; Algohani, Turki; Fallatah, Ibrahim; Daghriry, Mohammed Y.; Alharbi, Rawan K.; Alhafaf, Hassan; Talal, Madi; et al. (Frontiers in Genetics, 2025)
BackgroundSitosterolemia and Familial hypercholesterolemia (FH) represent two genetically distinct lipid metabolism disorders marked by disparate inheritance mechanisms and therapeutic responses. It is typically inherited in an autosomal dominant pattern due to mutations in the low-density lipoprotein receptor (LDLR) gene, whereas sitosterolemia follows an autosomal recessive mode associated with mutations in the ATP-binding cassette transporters (ABCG5 and ABCG8). To the best of our knowledge, the presence of both disorders within the same family has never been documented in the scientific literature.ObjectiveIn this paper, we report what is likely the first genetically confirmed case of compound heterozygosity involving both sitosterolemia and familial hypercholesterolemia in a Saudi Arabian consanguineous family. This unique case highlights the complex diagnostic challenges and therapeutic considerations in managing overlapping dyslipidemia phenotypes.MethodsA multigenerational family was recruited from the Diabetes and Endocrinology Center in Jazan, Saudi Arabia. Comprehensive clinical evaluations were conducted, including family history, physical examination, and lipid profiling. Whole exome sequencing (WES) was performed using the CentoXome® platform with >98% of targeted bases covered at ≥20x, followed by bioinformatics analysis via a standardized pipeline. Sanger sequencing validated the identified variants. Variant pathogenicity was evaluated using in silico tools such as SpliceAI, REVEL, MetaLR, and SIFT, alongside conservation and gene expression data. Statistical analysis of lipid levels pre- and post-treatment was conducted using paired t-tests, with significance set at p < 0.05. Notably, direct measurements of plant sterols were not performed.FindingsWES revealed a novel heterozygous frameshift deletion in LDLR and a pathogenic splice site variant in ABCG8, consistent with compound FH and sitosterolemia. The proband responded remarkably to ezetimibe monotherapy, while his children required combination therapy with high-intensity rosuvastatin and PCSK9 inhibitor Evolocumab for LDL-C reduction. Structural modeling and molecular docking analyses revealed altered ligand-binding affinities in mutant proteins, providing a plausible structural explanation for the observed variation in drug response.ConclusionThis study presents the first extensive molecular characterization of a dual FH-sitosterolemia phenotype. It emphasizes the critical role of genomic diagnostics in managing complex lipid disorders and supports personalized medicine approaches, especially in consanguineous populations where blended phenotypes may be underrecognized.